A 90th anniversary of the Irkutsk Organization of the Union of Architects of Russia - Druzhinina, Inna (project baikal, 2025)
The article gives a brief overview of the gala evening dedicated to the 90th anniversary of the Irkutsk Organization of the Union of Architects of Russia. The holiday scenario highlights its traditions and innovations. The author shares her impressions, emotions and expresses her wishes.